Out of poverty : what works when traditional approaches fail - Polak, Paul (BK currents book., 2008)
The author explores some of the methods by which governments are attempting to eradicate world poverty and why they have been unsuccessful; and describes how he and others have developed low-cost tools to help poor farmers become more self-sufficient.